2018
DOI: 10.1016/j.desal.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Process modeling for economic optimization of a solar driven sweeping gas membrane distillation desalination system

Abstract: Water scarcity is especially impactful in remote and impoverished communities without access to centralized water treatment plants. In areas with access to a saline water source, point-of-use desalination by solar-driven membrane distillation (MD) is a possible method for mitigating water scarcity. To evaluate the applicability of MD, a comprehensive process model was developed and used to design an economically optimal system. Thermal energy for distillation was provided by solar thermal collectors, and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…This section provides a cost comparison between solar powered MD and other technologies, and then focuses on new developments in nanostructured photothermal materials for solar powered MD. A cost process model for solar powered MD is shown in Moore et al developed a process model to simulate a solar powered sweeping gas MD system powered by both solar thermal and PV [174]. They found the cost of water for an optimized system to be $85/m 3 .…”
Section: Membrane Distillationmentioning
confidence: 99%
See 1 more Smart Citation
“…This section provides a cost comparison between solar powered MD and other technologies, and then focuses on new developments in nanostructured photothermal materials for solar powered MD. A cost process model for solar powered MD is shown in Moore et al developed a process model to simulate a solar powered sweeping gas MD system powered by both solar thermal and PV [174]. They found the cost of water for an optimized system to be $85/m 3 .…”
Section: Membrane Distillationmentioning
confidence: 99%
“…Comparison of reported MD water production costs as function of production volume per day(adjusted for inflation)[174,175] shows water production cost as a function of production volume for different MD studies, although these include systems with varying configuration, energy source and cost models.Table 3shows a comparison of levelized cost of water (LCOW) from conventional SWRO and solar powered MD. It can be seen that the LCOW from solar powered MD is still a long away from being economically competitive.…”
mentioning
confidence: 99%
“…Where x is the index data value to be normalized, max(V) and min(V) are the maximum and minimum values in the index data, and y is the converted result. The SVM classifier uses a non-linear mapping θ on the normalized sample set to map the data into a high-dimensional feature space and perform linear regression processing [36]. The regression function was:…”
Section: A Support Vector Machinementioning
confidence: 99%
“…Applying metallic hollow fibers or a coating membrane with polydimethylsiloxane could significantly enhance the water vapor permeate flux up to 40% in sweep gas membrane distillation [65]. Moore et al [66] developed a non-steady process model to simulate an SGMD system integrated with solar thermal and photovoltaic power for the desalination of drinking water. The economic analysis indicated that the optimized proposed technology for cost recovery over a 20-year service life is 84.7 $/m 3 , which is more than alternative sources water costs.…”
Section: Sweeping Gas Membrane Distillation (Sgmd)mentioning
confidence: 99%